Social Entreprenurship Pesantren (The Analysis of Argumentative Local Wisdom of Dayah in Aceh) - Iswan Fadlin; Taufiq Taufiq (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
The objective of conducting this research is to analyze and investigate social entrepreneurship at Islamic boarding schools (Pesantren), which deals with economic independence, social influence, and strengthening religious values. It is significant that Dayah's local wisdom dimensions act as propelling pillars of transformation towards realizing the pesantren's socio-economic independence. The main objective of this research is to examine the active role of the local wisdom possessed by Dayah that contributed to its success in transitioning pesantren from "surviving" to "thriving." Thus, the research adopts a qualitative ethnographic approach. This method is used to investigate narratives, interactions, and representations in the Dayah community in order to understand the manner by which local wisdom functionally forms and legitimates practices of social entrepreneurship. The findings above show that pesantren possess managerial inertia, which can be explained by a conservative mentality or resistance to new ideas. Dayah's local knowledge functions as an "effective hammer" in overcoming the internal barriers and nurturing a value-based entrepreneurial culture. The above research findings offer a replicable model in creating social entrepreneurship in relation to intersectional cultures/spirituality, especially religious educational environments. The above findings offer an original approach to dealing with pesantren and can be used as guideline for community empowerment policy with local values.